Quality Evaluation of the Care Process for Type 2 Diabetics - Addys Díaz Piñera; Lisbeth Fernández González; Armando Rodríguez Salvá; Armando Humberto Seuc Jo; Nelsy Álvarez Mesa (Revista Finlay)
Background: diabetes mellitus is a serious health problem with an upward trend. Every year a considerable number of people die as a result of their complications that derive from poor control, so improving the quality of care constitutes a challenge for health systems. Objective: to evaluate the quality of care by reviewing the medical records and investigating some of the program indicators, in a health area of the Cárdenas municipality during 2016. Method: an investigation of health systems and services was carried out, using a two-stage conglomerate sampling. The variables studied were related to the fulfillment of the main activities established in the patient care process and others with the knowledge, training and satisfaction of the providers. Instruments tested in previous studies were applied. The statistical packages Access 2000 and SPSS 21.0 were used to collect and analyze the results. Results: the evaluation of the process, level of knowledge, training and satisfaction of the suppliers was not adequate in the studied area, as the proposed standards were not reached for any of the criteria. Conclusions: the care received by these patients is not adequate since there were difficulties in the fulfillment of the program, which affected on its follow-up and control.